The Holocaust in the borderlands Interethnic relations and the dynamics of violence in occupied Eastern Europe - Fisher, Gaëlle 1985-; Mezger, Caroline 1987-; International workshop "The Holocaust in the Borderlands: Interethnic Relations and the Dynamics of Violence in Occupied Eastern Europe" (European Holocaust studies, 2019)
Gaëlle Fisher and Caroline Mezger: Introduction - The Holocaust in the Borderlands: Interethnic Relations and the Dynamics of Violence in Occupied Eastern Europe -- Anca Filipovici: The Rise of Antisemitism in the Multiethnic Borderland of Bukovina: Student Movements and Interethnic Clashes at the University of Cernauti (1922-1938) -- Doris L. Bergen: Saving Christianity, Killing Jews: German Religious Campaigns and the Holocaust in the Borderlands -- Linda Margittai: Hungarians, Germans, and Serbs in Wartime Vojvodina: Patterns of Attitudes and Behaviors towards Jews in a Multiethnic Border Region of Hungary -- Goran Miljan: The Ustasha Youth and the Aryanization of Jewish Property in the Independent State of Croatia, 1941-1945 -- Svetlana Suveica: Local Agency and the Appropriation of Jewish Property in Romania's Eastern Borderland: Public Employees during the Holocaust in Bessarabia (1941-1944) -- Anna Wylegala: Listening to the Different Voices: Jewish, Polish, and Ukrainian Narratives on Jewish Property in Nazi-Occupied Eastern Galicia -- Miriam Schulz: „Gornisht oyser verter"?! Khurbn-shprakh as a Mirror of the Dynamics of Violence in German-Occupied Eastern Europe -- Source Commentary -- Sanela Schmid: Law Decree on Racial Affiliation (April 30, 1941) int he Independent State of Croatia -- Project Descriptions -- Elysa Ivie McConnell: Fascist Italy and the "Other": Italianization and the Holocaust in the Triveneto Borderlands, 1918-1948 -- Frank Görlich: Vanishing Point Transnistria: Post-Imperial Biographies and German Transnational Continuities in an Age of Empire-Building and Ideologized Mass Violence -- Dana Mihailescu: Transcultural Networks in Narratives about the Holocaust in Eastern Europe.